Usulan Perbaikan Kualitas Proses Produksi di Industri Berbasis Hasil Laut - Gidion Karo Karo; Martin Ryanche (Universitas Bunda Mulia, 2017)
This Research was aimed to give a suggestion how to improve production process’s quality in PT. Biru Laut Nusantara. Realizing that fish processing needs a lot of precision because of food quality and safety problem, this research will show the cause of the defect and how to solve the problem. This research focused on identifying the types and factors which causing defective products and getting the solution in maintaining and improving the quality of production process by using HACCP Approaching and Six Sigma. Some of the quality tools that used in this research are Check Sheet, Pareto Charts, Fishbone Diagram, P Chart, and FMEA. The results show that PT. Biru Laut Nusantara’s capability process is lower than 1, which is need to be improved. The solution will be focused solving temperature (35%), hard impact (30%), and contamination (20%) defect factor. The result shows us that QC department still needs a lot of training and some new standard like GMP and SSOP must be implemented. The discussion with the company’s QC department concludes that if the suggestion from the research is implemented, it will decrease defect rate about 10%-90%.Keywords: Quality Control, HACCP, Six Sigma, Quality Tools, Capability Process, Good Manufacturing Procedures, Standard Sanitation Operating Procedures.